Half-Heusler alloys: Enhancement of ZT after severe plastic deformation (ultra-low thermal conductivity). (15th January 2020) - Rogl, Gerda; Ghosh, Sanyukta; Wang, Lei; Bursik, Jiri; Grytsiv, Andriy; Kerber, Michael; Bauer, Ernst; Mallik, Ramesh Chandra; Chen, Xing-Qiu; Zehetbauer, Michael; Rogl, Peter
Abstract: Several n - and p -type Half-Heusler (HH) thermoelectric materials (Ti0.5 Zr0.5 NiSn-based and NbFeSb-based) have been processed by high-pressure torsion (HPT) to improve their thermoelectric performance via a drastic reduction towards ultra-low thermal conductivity. This reduction occurs due to grain refinement and a high concentration of deformation-induced defects, i.e. vacancies and dislocations as inferred by this severe plastic deformation and documented via SEM and TEM investigations. In most cases the figure of merit, ZT, and the thermo-electric conversion efficiency were enhanced up to η ∼ 10% for the thermally stable HPT-processed sample. Raman spectroscopy, backed by DFT calculations, proves that HPT induces a stiffening of the lattice and as a consequence, a blue-shift of the lattice vibrations occurs. Furthermore for all investigated specimens Vickers hardness values after HPT were significantly higher, whereas the change in the elastic moduli was less than 5% in comparison to the HP reference sample. Graphical abstract: Image, graphical abstract